Probiotic application in fermentation of fish feed materials: a review: Probiotic application in fermentation of fish feed materials: a review - Yuli Andriani; Rusky Intan Pratama (Universitas Muhammadiyah Malang, 2022)
Feed is an essential component in fish farming because it supports the survival and growth of fish. Provision of feed, one of which can be done through the utilization of organic waste. One of the efforts used to improve the nutritional quality of feed ingredients is the fermentation technology using probiotic bacteria. The probiotic microbes used in the fermentation will overhaul the structure of the organic matter and the complex bonds contained in the feed ingredients. This right will lead to an increase in the quality of feed ingredients, and in turn, the product will be easily digested and meet the nutritional needs of fish. Search results in several studies indicate several types of microbes involved in probiotic fermentation, either singly or in consortia. Some of them are derived from the Bacillus, Lactobacillus and Saccharomyces groups. Applying probiotics in the fermentation process of feed ingredients can improve their nutritional quality. Examples of some common feed ingredients used in the fermentation process are coffee husk waste, banana peel waste, peanut shell waste, rice straw and coconut cake.